Tracing the Idea of Fit and Healthy Students in the thoughts of Some Eminent Educationalists of India - Gupta, Ritesh (JOURNAL OF INDIAN EDUCATION, 2021)
Studying the history of education develops a better understanding of the educational problems we are facing today. Most importantly, it offers an entry point to deal with contemporary educational questions, thus, paving the way to frame the right educational policies. The matter of student’s health and fitness has always been central to educational philosophies and policies in India. With the goal of healthy and fit students, the honourable Prime Minister Shri Narendra Modi has initiated Fit India Movement in schools all over the country. Considering the importance of Fit India Movement, this paper proposed to trace the idea of healthy students in the educational thoughts of our educationalists, viz. Swami Vivekananda, Sri Aurobindo, Madan Mohan Malaviya, Lala Lajpat Rai and Syama Prasad Mukherjee. The paper would reveal about the health and fitness of Indians, with reference to the philosophies and arguments of these educationalists who appealed for the inclusion of physical education and sports in schools, colleges, and universities of India.